A feedback regulation between Kindlin‐2 and GLI1 in prostate cancer cells. Issue 6 (18th January 2013) - Gao, Jianchao; Khan, Ammad Aslam; Shimokawa, Takashi; Zhan, Jun; Strömblad, Staffan; Fang, Weigang; Zhang, Hongquan
Abstract : Kindlin‐2 is engaged in tumor progression. However, the mechanism accounting for Kindlin‐2 regulation in tumor cells remained largely unknown. Here, we report a regulatory loop between Kindlin‐2 and GLI1, an effector of Hedgehog signaling pathway. We show that Kindlin‐2 is transcriptionally downregulated via GLI1 occupancy on the Kindlin‐2 promoter. Adversely, we found that Kindlin‐2 promotes GLI1 expression through a mechanism involving GSK3β inactivation and is independent of Smoothened. Functionally, knockdown of Kindlin‐2 cooperates with cyclopamine, a Smoothened antagonist, to decrease the viability of prostate cancer cells. Taken together, targeting the Kindlin‐2–GLI1 feedback loop may facilitate the killing of prostate cancer cells. Abstract : ► Gli1 specifically occupies Kindlin‐2 promoter and inhibits the transcription of Kindlin‐2. ► Kindlin‐2 promotes the expression of Gli1 independent of Hedgehog activator Smoothened. ► Kindlin‐2 knockdown facilitates the sensitivity of prostate cancer cells to cyclopamine induced prostate cancer cell death.